Comparison of classic and novel human astrovirus MLB and VA seroprevalence in HIV and non-HIV cohorts in South China demonstrates high seroreactivity to classic human astrovirus, which is associated with HIV infection - Jianhao Wang; Binyi Liu; Sisi Liu; Yawen Sun; Ruiying He; Yun Lan; Linna Liu; Hongbing Jiang (Microbiology Spectrum)
ABSTRACT Human astroviruses (HAstVs), including classic and novel clades (MLB, VA), are enteric pathogens with increasing clinical significance, particularly in immunocompromised populations. This cross-sectional study investigated HAstV seroprevalence and antibody response profiles in 197 individuals (101 HIV-positive and 96 HIV-negative) from Guangdong Province, South China. Recombinant HAstV1, MLB2, and VA1 spike proteins were expressed in Escherichia coli, structurally validated using AlphaFold2, and used in enzyme-linked immunosorbent assays-based serology with minimal cross-reactivity confirmed in murine models. Cohort study showed that HIV-positive individuals exhibited significantly higher HAstV1 seroreactivity (median OD450: 0.93 vs 0.64, P = 0.047) and an ordinal logistic regression revealed greater odds of stronger antibody responses to HAstV1 (adjusted odds ratio [aOR] = 1.91, P = 0.027). In contrast, VA1 seroprevalence was lower in HIV-positive participants (median OD450: 0.73 vs 1.02, P = 0.026), with reduced odds of high reactivity (aOR = 0.61, P = 0.089). In addition, VA1 demonstrated the highest overall seroprevalence (78.68%), followed by MLB2 (77.16%) and HAstV1 (75.13%), and significant associations between co-exposure to MLB2 and VA1 were observed by regression analysis (aOR = 1.60, P = 0.010). Together, these findings highlight distinct HIV-associated seroreactivity shifts in HAstV immunity, underscoring the regional importance of classic HAstV1 and the need for clade-specific surveillance in high-risk populations.IMPORTANCEHuman astroviruses (HAstVs) are increasingly implicated in severe systemic and neurological infections, yet their seroepidemiology in immunocompromised populations remains poorly characterized. This study provides critical insights into the divergent immune responses to classic and novel HAstV clades among people living with HIV (PLWH) in southern China. We demonstrate that PLWH displayed heightened antibody responses to classic HAstV1 but reduced reactivity to MLB2, suggesting HIV-driven immune dysregulation may selectively boost infection with classic HAstV strains. These findings highlight the need for targeted surveillance and improved diagnostics for HAstV infections in high-risk populations.